Phytosociological survey of the Lihue Calel national park, La Pampa, Argentina (Semiárida, 2020)
The Lihue Calel National Park is situated in the center of La Pampa (long. 65° 39' W and 65°33' W, lat. 37° 54' S and 38° 05' S). The clima is mild, semiarid with an annual rain of 400 mm. The texture of the soil is loamy-sand, sandy-loam - and sandy. The landscape includes different geoforms (to P. Little hills. base of the hills. slopes and depressions) each of them characterized by a definite kind of vegetation. Thirteen different communities were distinguished. Of each of them, situation topography, formation, physiognomy, structure, stratification and floral composition were described.
Keywords: Lihue Calel National Park